Pilot Study of Radiation-induced Gastrointestinal Injury in a Hemi-body Shielded Göttingen Minipig Model. Issue 1 (January 2018) - Measey, T.J.; Pouliot, M.; Wierzbicki, W.; Swanson, C.; Brown, D.; Authier, S.; Donini, O.
Abstract : Abstract: Development of medical countermeasures (MCMs) for gastrointestinal (GI) injury following acute radiation exposure requires well-characterized models that can assess not only survival but also secondary endpoints, including structural and functional characteristics of GI damage and recovery that ultimately contribute to long-term survival. The authors conducted a pilot study in a hemi-body shielded Göttingen minipig model of radiation-induced GI injury that enables radiation damage to the GI tract to be evaluated and reduces the potential for hemorrhage and/or damage in other more sensitive organ systems. With shielding of the head, chest, and front legs, radiation dose levels of 14 Gy were required to see significant GI-related morbidity, while dose levels of 16 Gy resulted in significant mortality by day 45 post-irradiation. Periodic scheduled necropsies showed significant reduction in and slow recovery of intestinal crypt count at 14 and 16 Gy. Intestinal proliferative activity was initially increased and then gradually decreased over the course of the study. Histological evidence of marked inflammatory infiltrates was noted in the GI tract at day 5, while collagen deposition, indicative of fibrosis, was observed as early as day 15, peaking at day 30. The radiation dose-responsive indicators of GI damage identified in this model (i.e., intestinal crypt count and proliferative activity) may serve as useful endpoints for evaluation of the efficacy of potential MCMs. Abstract : Supplemental digital content is available in the text.